Interference mitigation by power optimisation & frequency reuse on femtocell LTE network: article / Muhamad Fadhlan Md Ramli - Md Ramli, Muhamad Fadhlan (2016)
This paper present the analysis of interference mitigation method on femtocell in LTE network. Femtocell deployment required to provide better coverage for user in building. The simulation by power measurement & frequency reuse using EXata Qualnet 5.3. The simulation results conclude the mitigation technique can reduce the interference and give better user experiences.